Guiding the Ruler: Insights into Islamic Mirrors for Princes and Concepts of Governance - Lohlker, Rüdiger (FISIP UIN Sunan Gunung Djati Bandung, 2024)
Research Problem: Islamic ideas on rulership and governance are disseminated through various textual traditions, among which the mirrors for princes genre holds a prominent place. These texts, serving as manuals for rulers and future leaders, encapsulate a blend of ethical, spiritual, and practical guidance. However, there is a lack of clarity regarding the nature of this genre, particularly its integration of religious and political dimensions, as well as its significance in shaping Islamic thought on governance. Research Purposes: This study aims to explore the historical and cultural development of the mirrors for princes genre, analyze its content to uncover insights into Islamic rulership, and challenge the notion that this genre is quasi-secular by highlighting its intrinsic connection to Islamic principles. Research Methods: The research employs a qualitative approach, drawing on a comprehensive review of primary and secondary sources within the mirrors for princes tradition. Historical analysis and textual interpretation are utilized to examine the themes, structures, and intended purposes of these works across different Islamic contexts. Results and Discussion: The study reveals that mirrors for princes are deeply embedded in Islamic ethical and political thought, offering rulers guidance that intertwines religious obligations with administrative responsibilities. These texts emphasize the ruler's role as a moral and spiritual guide, as well as a political leader. The research demonstrates the diversity of traditions that contributed to the genre and highlights its adaptability across time and regions in the Islamic world. Research Implications and Contributions: This study contributes to a deeper understanding of Islamic political and ethical thought, emphasizing the mirrors for princes genre as a vital source of historical insights into governance. It challenges secular interpretations by illustrating the genre's rootedness in Islamic values and its role in shaping the ideals of rulership. The findings provide a foundation for further research into the interplay between religion and politics in Islamic history and offer valuable perspectives for comparative studies in governance and leadership.